Estuarine habitat use by the California sea otter (Enhydra lutris nereis) - Lindsey, Jacqueline Kimberly (San Jose State University, 2017)
As the southern sea otter (Enhydra lutris nereis) range expands into northern and southern California, it will encounter estuaries that have been historically occupied by sea otters. Understanding how otters use re-colonized estuarine environments will inform how estuaries might be managed to encourage future sea otter range expansion. This project addressed the question: how do southern sea otters use space in the unique estuarine habitats of Elkhorn Slough? I compared the locations and behaviors of 25 individual sea otters of different status (male, female, and female with pup) among eelgrass, saltmud, saltmarsh, tidal creek, and main channel habitats in Elkhorn Slough. From these data I created a synoptic model to predict space use for resident otters of Elkhorn Slough based on sex, behavior, home range, and habitat distribution. Ninety percent home ranges calculated from the model indicated that females used larger home ranges than males in the slough, but both sexes had smaller home range areas than otters using the rocky outer-coast habitats of the Monterey Peninsula. In Elkhorn Slough, important habitats associated with resting included tidal creeks (for females only) and eelgrass, whereas the main channel was important for foraging behaviors of both sexes. Although using land habitats, sea otters were most likely to be found within 50 m of water. Protection of similar resting and foraging habitats in prey-rich estuaries colonized in the future will promote southern sea otters recovery by allowing them to re-colonize historically important estuarine habitats.